(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Organizational management and quality culture have evolved as strategic pillars for institutional strengthening in competitive and dynamic environments. From an accounting perspective, these elements make it possible to integrate efficiency into processes with financial transparency and accountability. This article proposes an integrated approach that links managerial accounting with quality management, highlighting how accounting information systems can become strategic tools to ensure sustainability, credibility and continuous improvement. The results show that the adoption of quality practices supported by accounting data not only improves operational efficiency, but also strengthens institutional trust and evidence-based decision-making.